Measuring the Impact of Economic Development on Environmental Degradation: an Empirical Analysis in Indonesia (Journal of Economic Education, 2022)
This study aims to analyze the effect of economic growth, human development index, population density, land transportation and housing percentage on environmental quality in Indonesia. This research is a quantitative study with the data used is secondary data in the form of provincial panel data in Indonesia for the 2015-2019 period which is sourced from the Central Statistics Agency and also the Ministry of Environment. The data analysis technique used in this research is panel data regression analysis. Based on the results of panel data regression analysis, it can be explained that the variable economic growth has a negative and significant effect on the environmental quality index in Indonesia with a coefficient value of -0.013256. The human development index variable has a positive but not significant effect on the environmental quality index in Indonesia with a coefficient value of 0.045169. The population density variable has a negative and significant effect on the environmental quality index in Indonesia with a coefficient value of -1.214671. The land transportation variable has a negative and significant effect on the environmental quality index in Indonesia with a coefficient value of -2.142561. The land transportation variable has a negative and significant effect on the environmental quality index in Indonesia with a coefficient value of -1.134162. The government as the competent authority in policy formulation must start from an early age paying attention to environmental elements in future development planning. The community needs to increase their awareness in preserving the environment by participating in efforts to reduce pollution and pollution by carrying out environmentally friendly activities.